EKONOMI-POLITIK HUTAN KEMASYARAKATAN (Kajian Pengelolaan Hutan berbasis Hak-Hak Produktif Masyarakat Sekitar) - Ahmad Muttaqin (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2013)
The main problem in managing forest, particulary in Java, is that local communitiesliving in and/or around forest are less involved. Meanwhile, it is clear that local communitiesdepend heavily on forest resources. So, when forest are not acceseble for them, their continuityof life is thretened. Managing forest resources together with community (PHBM) is a newpattern for forest management in Java. The principle of this pattern is collectivenness betweenlocal communities and Perum Perhutani with others sides that have interest using the spirit ofsharing (right and obligation). The realtion formed in such pattern is based on modern way ofworking in which work division and funcional specification are implemented. Labour isdistributed into work division that are funcionally.The problem occurs because positions in modern way of working that is implemented inPHBM are determinate by the contibution of production factors. The are 4 production factors inPHBM i.e capital, land/location, technology, and labour. These influence significanly on relationof production. Capital is accounted as the most important factor in all production processes. Thebigger capital contributed by a person, the higher position of the person in PHBM.Economic-politicall approuch tries to see political tendency in PHBM from economicalpoint of view. Discourse that is launched by PHBM is welfare for local communities throughparticipation of the communities in managing forest. At glance, the principe of sharing indicatedthat the potency of welfare for coomunities can be realized, but if the proportion shared forcommunities is too low, 25 % of the value and proportion of production factors, the welfarewwill be more difficult to be reached. From PHBM point of view, the possible production factorsthat can be given by communities is only â€œlabourâ€. In the process of production, labourâ€™sproportion and value is only 20 %. Thus, the relation of production has less ability to give justicefor communities.